Insulin action in primary hyperaldosteronism before and after surgical or pharmacological treatment - Šindelka, G.; Widimský, J.; Haas, T.; Prázný, M.; Hilgertová, J.; Škrha, J. (Experimental and Clinical Endocrinology & Diabetes, 2000)
The relationship between arterial hypertension and insulin resistance has long been established. We used primary hyperaldosteronism as a model of the relationship between secondary hypertension and insulin sensitivity. Our group consisted of 9 patients with arterial hypertension caused by primary hyperaldosteronism. Five of these patients with aldosterone producing adenoma were operated on and four patients with idiopathic hyperaldosteronism were treated with spironolactone. Hyperinsulinaemic euglycaemic clamp technique was performed before and at least 6 months following the treatment to evaluate the insulin action. Significantly lower glucose disposal rate (M), insulin sensitivity index (M/I) and decreased metabolic clearance rale of glucose (MCRG) were found in patients before treatment as compared to healthy controls. In both treated groups the blood pressure and plasma potassium concentrations returned to normal values, whereas plasma aldosterone levels were normalised only after surgical removal of the adenoma. Significantly improved insulin action (M/I: 30.2 ± 5.9 vs. 51.4 ± 12.2 μmol.kg−1.min−1 per mU.1−1 × 100, p = 0.017) was observed in patients after operation of aldosterone producing adenoma. In contrast, spironolactone treatment of patients with idiopathic hyperaldosteronism did not significantly influence insulin action (M/I: 24.5 ± 7.3 vs. 18.7 ± 7.6 μmol.kg−1.min−1 per mU.1−1 × 100, p = 0.198). Since plasma aldosterone concentrations have been normalised only in patients after removal of the adenoma whereas they remained increased in spironolactone treated group, we suppose that aldosterone itself could play a role in the development of impaired insulin action.
Keywords: primary hyperaldosteronism; insulin resistance; hyperinsulinaemic euglycaemic clamp